Institutional Lifelong Learning Initiatives and Their Impact on Teachers' Sustainable Professional Development: na - Eunice Mareth Querol Areola, PhD HSG; Maria Urduja Galang (Journal of Sustainable Community Development (JSCD), 2026)
This study argues that teachers’ positive attitudes toward lifelong learning and professional development are crucial predictors of their actual engagement in such initiatives. It investigated the relationship between these attitudes and teachers' participation in lifelong learning and professional development initiatives at a private elementary school in Quezon City. Using a descriptive-correlational research design, the study surveyed 42 teacher respondents through a researcher-designed Likert-scale questionnaire covering three dimensions of lifelong learning initiatives—workshops and seminars, continuing professional education, and reflective practice—and three dimensions of professional development programs—peer mentoring/coaching, classroom observation, and focus group discussions/collaboration. Results indicated that the majority of respondents were female, 29 years old or younger, held a bachelor’s degree, and had five years or less of teaching experience. Statistical analysis revealed a significant positive relationship between teachers’ attitudes and their extent of practice in both lifelong learning (r = 0.632, p < .001) and professional development (r = 0.701, p < .001). Teachers who valued seminars, workshops, continuing education, and reflective practices actively engaged in these activities, applied new strategies in the classroom, and sought opportunities for professional growth. Similarly, teachers with positive attitudes toward mentoring, coaching, classroom observation, and collaborative discussions demonstrated higher participation and commitment to professional development. These findings highlight the critical role of teachers’ attitudes in promoting engagement with lifelong learning and professional development programs, emphasizing the need for school administrators to foster supportive, collaborative, and reflective environments that enhance instructional competence and continuous professional growth.